Functioning of Neural Systems Supporting Emotion Regulation in Anxiety-Prone Individuals - Campbell-Sills, Laura (2010)
Previous neuroimaging studies suggest that prefrontal cortex (PFC) modulation of the amygdala and related limbic structures is an underlying neural substrate of effortful emotion regulation. Anxiety-prone individuals experience excessive negative emotions, signaling potential dysfunction of systems supporting down-regulation of negative emotions. We examined the hypothesis that anxious individuals require increased recruitment of lateral and medial PFC to decrease negative emotions. An emotion regulation task that involved viewing moderately negative images was presented during functional magnetic resonance imaging (fMRI). Participants with elevated trait anxiety scores (n = 13) and normal trait anxiety scores (n = 13) were trained to reduce negative emotions using cognitive reappraisal. Blood oxygenation level-dependent (BOLD) changes were contrasted for periods when participants were reducing emotions versus when they were maintaining emotions. Compared to healthy controls, anxious participants showed greater activation of brain regions implicated in effortful (lateral PFC) and automatic (subgenual anterior cingulate cortex) control of emotions during down-regulation of negative emotions. Left ventrolateral PFC activity was associated with greater self-reported reduction of distress in anxious participants, but not in healthy controls. These findings provide evidence of altered functioning of neural substrates of emotion regulation in anxiety-prone individuals. Anxious participants required greater engagement of lateral and medial PFC in order to successfully reduce negative emotions.